The Implementation of Kurikulum Merdeka in Islamic Education in the 3T Regions of North Lombok - Hakim, M. Ikhwanul; Alfitri, Bahya (MODELING: Jurnal Program Studi PGMI, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum in the 3T (isadvantaged, forefront, outer) regions of North Lombok. The method employed is qualitative with a multi-site approach to examine the challenges of implementing the Merdeka Curriculum in this area. The study finds that the implementation faces challenges such as inadequate educational infrastructure, limited teacher quality, and high levels of poverty, which hinder effective education. To address these issues, strategic collaboration among local government, educational institutions, and the community is crucial. This includes improving infrastructure, providing continuous teacher training, integrating local content into the curriculum, and enhancing socio-economic support and transportation. Active parental involvement also plays a significant role. Through these combined efforts, inclusive and relevant education can be achieved for students in these regions.